Lampung Natural Zeolite as a Green Solution: Heavy Metal Waste Treatment through Flotation-Filtration Method - Asep Setiawan (Cahaya Ilmu Cendekia Publisher, 2024)
Purpose of the study: This study aims to evaluate and compare the effectiveness of flotation, filtration, and combined flotation–filtration processes in removing iron (Fe) and reducing Chemical Oxygen Demand (COD) from synthetic wastewater. Methodology: This study employed flotation, filtration, and combined flotation–filtration methods using a ceramic membrane filtration unit, vacuum pump, air–ozone generator, and synthetic wastewater containing Fe, zeolite, Sodium Lauryl Sulfate (SLS), and Poly-Aluminum Chloride (PAC). Data were analyzed using concentration measurement and percentage removal efficiency calculations. Main Findings: The combined flotation–filtration process showed the highest performance, achieving Fe removal efficiency of 94.74% with final concentration of 5.26 mg/L. Filtration and flotation showed lower efficiencies. COD reduction was more stable in filtration but more effective initially in flotation–filtration. Membrane fouling was lower in flotation–filtration, resulting in higher permeate volume compared to filtration alone. Novelty/Originality of this study: This study presents a simultaneous flotation–filtration system integrated with air–ozone injection to enhance pollutant removal and reduce membrane fouling. It highlights the dual role of air–ozone as an oxidizing and cleaning agent, offering improved efficiency and membrane durability compared to conventional single-process methods.